THE USE OF AUTHENTIC MATERIALS IN TEACHING ENGLISH: INDONESIA TEACHERS’ PERSPECTIVE IN EFL CLASSES - Huda, Miftahul (PEOPLE: International Journal of Social Sciences, 2017)
This study aimed to investigate Indonesian EFL teachers’ beliefs regarding the use of authentic materials at State Islamic Junior High School level in South Tangerang. Six English teachers took part in completing a survey questionnaire and interview for the purpose of this study. The results indicated that although most English teachers have positive attitude toward using authentic materials in the classroom and preferred to use authentic materials. The analysis showed that some of the teachers concernabout selecting materials of AMs and designing activities of using AMs in their classroom.The study has significant educational implications for English teacher for the further training using AMs recommendations for future study may focus on materials development using AMs including class observation and post class observation on how the teachers use authentic materials effectively.It is also suggested that the study should have more teachers from different schools involve in this study.